2017
DOI: 10.1111/bjc.12136
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of outcome monitoring in service users with psychosis: Findings from an Improving Access to Psychological Therapies for people with Severe Mental Illness (IAPTSMI) demonstration site

Abstract: Objectives Psychological therapy services are increasingly required to instate routine outcome monitoring (ROM), to demonstrate the clinical and economic impact of interventions. Professionals’ views of ROM are an acknowledged barrier to implementation. Service user perspectives have rarely been examined, but acceptability and perceptions of ROM are critical to successful implementation. We investigated service users’ experiences of ROM in an Improving Access to Psychological Therapies for people with Severe M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Moreover, again reflecting our findings, a recent study exploring service evaluation questionnaires (including the WEMWBS) used in the context of NHS-based psychological therapy found that service users suggested that these type of questionnaires may have some potential to elicit distress (Fornells-Ambrojo et al 2017). In this study, respondents mentioned how such measurement was seen as potentially intrusive and upsetting for those who are seeking support for a mental health related issue.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, again reflecting our findings, a recent study exploring service evaluation questionnaires (including the WEMWBS) used in the context of NHS-based psychological therapy found that service users suggested that these type of questionnaires may have some potential to elicit distress (Fornells-Ambrojo et al 2017). In this study, respondents mentioned how such measurement was seen as potentially intrusive and upsetting for those who are seeking support for a mental health related issue.…”
Section: Discussionsupporting
confidence: 80%
“…The role of clinical leadership is perceived as crucial in facilitating changes in service structures responsible for effective implementation of CBTp, which is corroborated by a recent pilot study (Fornells‐Ambrojo et al ., ). Similar to previous studies (Gray et al ., ; Jolley et al ., ), the findings highlight the championing nature that clinical leadership can take in order to facilitate CBTp implementation.…”
Section: Discussionmentioning
confidence: 97%
“…Techniques—ranging from Rorshach to symptom measures—were often experienced positively, helping people express themselves (particularly where spoken communication was difficult); gain clarity around feelings; positively reframe issues; and open space for thinking and reflection . Where people were ambivalent or disliked techniques, it was typically because they were lengthy, challenging, upsetting, inflexible or difficult to engage with .…”
Section: At the Assessmentmentioning
confidence: 99%